The Effect of Video Media on Learning Interest and Mathematics Learning Outcomes in Elementary School Students - Adriana Senga; Marwati Abd. Malik; Idha Novianti (PT ARRUS Intelektual Indonesia, 2023)
Now accessing videos on the internet so easy and today facilitates the learning process carried out by students. but the use of video as a medium for learning mathematics still needs to be analyzed for its effect on interest and learning outcomes obtained by elementary school students when learning is carried out. So, this experimental research aims to prove its effect. Data was collected using a questionnaire for learning interest and a test for learning outcomes which were both given before and after treatment. Data were obtained from 22 samples who were students of class Vc who were part of the fifth grade students of SD Negeri 292 Inpres Karangan which were used as the population. Through a quantitative approach with statistical data, it will be analyzed parametrically using the t test by comparing students' interests and learning outcomes before and after learning using video media. The use of video presents interactive, fun and easy-to-understand visual information for students. This is evidenced by the t-test on learning interest. The average difference is 33.33, with a score of sig.(2-tailed) 0.00 < 0.05. and the average difference in learning outcomes before and after learning is 50.45455, with a score of sig.(2-tailed) 0.00 < 0.05. which shows that there is an effect of using video media on students' interest and learning outcomes in mathematics